ANALYZING THE IMPACT OF THE BUSINESS LICENSING EASE POLICY FOR DRUG AND FOOD MSME BUSINESS ACTORS: A CASE STUDY IN EAST KALIMANTAN PROVINCE FROM 2018 TO 2023 - Wulandari, Ratih; Kenyowulan, Pranandari; Juwitaningsih, Marheni; Jaffar, Akhmad Kamaluddin (ipdn, 2023)
The limited number of products registered with the Indonesian FDA by MSMEs is primarily attributable to their ignorance of the procedures involved in obtaining product authorization. The Samarinda provincial office of the Indonesian Food and Drug Administration has launched the